Microsoft SQL Server 2008 R2 analytics & data visualization - Harts, Doug (McGraw-Hill, 2011)
"Effectively convey meaningful business insights to users across your enterprise with help from this practical guide. Written by a team of business intelligence experts, Microsoftʼ SQL Serverʼ 2008 R2 Analytics & Data Visualization shows how to achieve greater information absorption using the latest reporting tools. Learn how to build maps and gauges, integrate OLAP data, and develop dashboards. Security, performance tuning, and cloud computing techniques are also covered in this comprehensive resource"--Provided by publisher.